2013
DOI: 10.21450/rahis.v10i1.1862
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência Do Atendimento Do Sus Nas Microrregiões Do Estado De Santa Catarina

Abstract: RESUMOO objetivo deste estudo é avaliar a questão da eficiência do atendimento do SUS das vinte microrregiões do estado de Santa Catarina através da análise envoltória de dados (DEA). Esta pesquisa caracteriza-se como descritiva e com abordagem quantitativa. A amostra deste estudo é composta pelas 20 microrregiões de Santa Catarina. Os resultados desta pesquisa indicam que 65% das microrregiões pertencentes à amostra são eficientes. A média de eficiência do estado de Santa Catarina é de 97,04%. 75% das microrr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The small number of efficient cities was also observed in other studies 9,11,12,[25][26][27][28] , which found few or no efficient cities. In the assessment of structure efficiency, Barueri obtained the maximum assessment of "very high" efficiency in all years assessed.…”
Section: {(Rbest -Rcalc)} (Rbest -Rworst)supporting
confidence: 79%
See 1 more Smart Citation
“…The small number of efficient cities was also observed in other studies 9,11,12,[25][26][27][28] , which found few or no efficient cities. In the assessment of structure efficiency, Barueri obtained the maximum assessment of "very high" efficiency in all years assessed.…”
Section: {(Rbest -Rcalc)} (Rbest -Rworst)supporting
confidence: 79%
“…In order to assess the technical efficiency in the health structure management of the cities, the Health Technical Efficiency Index (HTEI) was used, likewise other studies 12,24,25 . Some studies have used the Data Envelopment Analysis (DEA) 9,11,24,[26][27][28][29] , which according to the authors, is limited by the benevolent analysis of the classic models, resulting in a great number of 100% efficient units (cities) and reducing the comparison between them 9,24,25 . One study used both methods for efficiency assessment 25 , showing that the results obtained by the HTEI were mostly compatible to the results obtained by the DEA method.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns estudos, realizados com Análise Envoltória de Dados (Data Envelopment Analisys -DEA), encontraram melhor eficiência. Foi o caso de estudo realizado em Santa Catarina com as vinte microrregiões de saúde (divisão válida de acordo com o plano diretor de regionalização da época do estudo), quando se constatou que 65% das microrregiões são eficientes (Politelo, Scarpin & Hein, 2013).…”
Section: Discussionunclassified